Divergent mind : thriving in a world that wasn't designed for you - Nerenberg, Jenara (HarperOne, 2019)
"A paradigm-shifting study of neurodivergent women-those with ADHD, autism, and other sensory processing differences-exploring why these traits are overlooked in women and how society benefits from allowing their unique strengths to flourish. As a successful, Harvard- and Berkeley-educated writer, entrepreneur, and devoted mother, Jenara Nerenberg was shocked to discover that her "symptoms" that were only ever labeled as anxiety were considered autistic and ADHD. Being a journalist, she dove into the research and uncovered neurodiversity-a framework that moves away from pathologizing "abnormal" versus "normal" brains and instead recognizes the vast diversity of our mental makeups. Divergent Mind is a long-overdue, much-needed answer for women who have a deep sense that they are "different." Sharing real stories from women with ADHD, autism, synesthesia, misophonia, and more, Nerenberg explores how these brain variances present differently in women and dispels widely held misconceptions. She also offers a path forward, describing practical changes in how we can communicate, design our surroundings, and better support divergent minds. When we allow our wide variety of brain makeups to flourish, we create a better tomorrow for us all"--